Pengaruh Tingkat Pendidikan Orang Tua Terhadap Prestasi Belajar Siswa MTs N 4 Lombok Timur - Annisa Aprilia (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
This research specifically aims to determine whether there was an effect of parental education level on student achievement at MTs N 4 East Lombok. Judging from the level of explanation, this research includes associative or relationship research. This study is a field research that uses quantitative methods with simple linear regression statistical techniques, using a significance level value of 5%. Based on the research objectives above, the results showed that: There was a significant influence between the level of parental education on student achievement at MTs N 4 East Lombok. This can be seen from the results of the analysis obtained with a significance level of 5%, obtained a Sig value of 0.000 <0.05, which means that the hypothesis in this study is accepted. The results of the coefficient of determination (R2) of 0.385 indicate that the influence of parents' education level on student achievement is 38.5%